(ERRATUM) Vulnerability Assessment at Mt. Bromo Indonesia by Using Time-Series Land Surface Deformation and GIS - Arliandy P. Arbad; W. Takeuchi; Y. Aoki; Ahmad Ardy (Applied Research on Civil Engineering and Environment (ARCEE), 2019)
This paper "Vulnerability Assessment at Mt. Bromo Indonesia by Using Time-Series Land Surface Deformation and GIS" Vol. 01 No. 01. pp. 24-30, August 2019, was erratum at because One of the requirements for submitting a paper for publication in this journal is a maximum plagiarism check result of 20%. However, the plagiarism level is still more than 20%, so the authors have improved so that the plagiarism check result is not more than 20%. Any data reuse must be cited appropriately. The scientific community has a very strong view of the matter and apologizes to the readers of the journal that this was not detected during the submission process. Depok, April 5, 2021 Editors